Pattern of rapid tranquillisation and restraint use in a central London mental health service. (31st July 2014) - Shepherd, Neil; Parker, Caroline; Arif, Nawal
Abstract: Rapid tranquillisation (RT) aims to quickly calm the severely agitated patient, in order to reduce the risk of imminent and serious violence to self or others. While it is widely used within mental health care settings, there is little published information on patterns of practice. Retrospective data collection identified a total of 2267 incidents of RT within the Central and North West London NHS Foundation Trust over a 19 month period equating to a mean frequency of approximately four incidents per day. These incidents mainly occurred in acute inpatient services and two and a half times more frequently in PICUs than on open wards. Of all the PICUS, the female PICU used most RT. Intramuscular RT was reported more often in most services. Restraint was used in 57% (n=1300) of RT incidents and minor injury resulted in only 11% of these incidents overall. There were no reports of major injury or death in the data set. Variations in RT use were seen across the Trust's geography and ward types.